Letter (copy) : Soap for Spain - Tewson, Vincent
030-0203-001 HVT/FC/EK/553. Secretary' s. 9th February, 1938. Mr. R. A. Palmer, Co-operative Union Ltd., Holyoake House, Hanover Street, MANCHESTER, 4. Dear Mr. Palmer, SOAP FOR SPAIN. I have your letter of the 8th February and the enclosed account for soap. We appreciate the facility which you were able to let us have in securing supplies of soap, and I have pleasure in enclosing herewith a cheque for £100. 1. 0. in settlement. Yours sincerely, Assistant Secretary. Cheque. 292/946/30/203